Business environment and public policy/ by P.C.Jain and N.K.Jain - "Jain, P.C." (Delhi, 1990)
This book is designed to equip a college student or business manager with the knowledge and skills that are necessary to handle the public policy dimension of job effectively. In recent years there has been a rapid growth of courses in Universities in "Business and Society" , Business and its Environment, 'Legal Environment of Business and other related subjects. It our hope that instructors of such courses and their students will find in this book all the basic issues which they find interesting and important.
Keywords: Environmental portection